Physicochemical properties influencing presence of Burkholderia pseudomallei in soil from small ruminant farms in Peninsular Malaysia - Musa, Hassan Ismail; Hassan, Latiffah; Shamsuddin, Zulkifli; Panchadcharam, Chandrawathani; Zakaria, Zunita; Abdul Aziz, Saleha (Public Library of Science, 2016)
Soil is considered to be a major reservoir of Burkholderia pseudomallei in the environment. This paper investigates soil physicochemical properties that may influence presence of B. pseudomallei in soil samples from small ruminant farms in Peninsular Malaysia. Soil samples were collected from the farms and cultured for B. pseudomallei. The texture, organic matter and water contents, pH, elemental contents, cation exchange capacities, carbon, sulfur and nitrogen contents were determined. Analysis of soil samples that were positive and negative for B. pseudomallei using multivariable logistic regression found that the odds of bacterial isolation from soil was significantly higher for samples with higher contents of iron (OR = 1.01, 95%CI = 1.00–1.02, p = 0.03), water (OR = 1.28, 95%CI = 1.05–1.55, p = 0.01) and clay (OR = 1.54, 95%CI = 1.15–2.06, p = 0.004) compared to the odds of isolation in samples with lower contents of the above variables. These three factors may have favored the survival of B. pseudomallei because iron regulates expression of respiratory enzymes, while water is essential for soil ecology and agent’s biological processes and clay retains water and nutrients.